Survivability of low pathogenic avian influenza virus in aqueous poultry manure fertilizer - Jennifer Schrock; Raksha Suresh; Olaitan Comfort Shekoni; Dina Bugybayeva; Sara Dolatyabi; Juliette Hanson; Frederick C Michel; Anne Dorrance; Gourapura J Renukaradhya (Journal of Applied Poultry Research)
SUMMARY: Avian influenza has been a growing problem in the United States for decades. Low pathogenic avian influenza (LPAI) virus causes low morbidity, while highly pathogenic avian influenza (HPAI) has a devastating effect on the poultry industry causing high morbidity and mortality worldwide. Manure from large and small poultry operations is spread on crop fields as a fertilizer. During an outbreak of avian influenza on a farm, it is critical to adequately process the manure to kill the virus before its use in agriculture. Aqueous extraction of poultry manure at high temperature (55-65°C) is an attractive method for the treatment of poultry manure, which extracts the nutrients and kills harmful microbes from the manure. The end product is a nutrient-rich liquid that can be safely applied to fields or used in hydroponic operations, with nutrients that are more bioavailable to the plant compared to dry litter. However, we do not know whether aqueous high temperature extraction processes completely kill the avian influenza virus present in the manure. Our aim in this study was to determine the competence of the aqueous extraction of poultry manure on avian influenza virus inactivation. We optimized the procedure using a LPAI virus isolate in a biosafety level 2 cabinet. Our data indicated that the LPAI virus including the hemagglutinin protein of the virus was completely destroyed when the poultry manure was processed by aqueous extraction at temperatures ≥ 55°C for one hour. Future research will identify the conditions required for inactivating the HPAI virus using this optimized procedure by performing the study in a BSL3 facility.